THE OPTIMIZATION OF EARLY DETECTION BY SAT INTELKAM TO PREVENT CRIMINAL ACTIONS UNDER THE JURISDICTION OF THE BOYOLALI POLICE - hafiz tengku said (Police Studies Review, 2022)
This research is motivated by the high number of criminal cases of stealing in the Boyolali Regency. In the last few years, the total number of criminal cases of stealing is high and has increased. Early detection efforts have been made, but criminal acts are still frequent. Therefore, a study was conducted that aims to describe and analyze the optimization of the implementation of detection activities by the Boyolali Police Intelkam Unit and what efforts are made in the implementation of early detection activities by the Boyolali Police Intelkam Unit. This research was conducted with a qualitative approach and using the field research method. Data was collected through interviews, observations, and document studies. The theory used is Management theory, SWOT theory, and Competency theory and the concept of early detection based on Perkabik No. 1 of 2013, and the concept of Sat Intelkam based on the Regulation of the National Police Chief Number 2 of 2021 concerning Organizational Structure and Work Procedures at the Resort Police and Sector Police. The results of the study found that the implementation of early detection had not run as expected. This is due to several obstacles in its implementation, including the condition of the Intelkam Unit which still lacks in terms of quality and quantity. Investigation of early detection that is not following Perkabik No. 1 of 2013, as well as external factors such as people who do not care about security and social order and lack of legal awareness by the community itself. The conclusion is that the implementation and efforts made in early detection activities to prevent the crime of stealing have not been optimal, the authors formulate several solutions to the problems faced by means and innovations that are formulated to optimize the implementation of early detection to prevent the crime of stealing.